How immigration affects investment and productivity in host and home countries - Volker Grossmann (IZA World of Labor, 2016)
Migration policies need to consider how immigration affects investment behavior and productivity, and how these effects vary with the type of migration. College-educated immigrants may do more to stimulate foreign direct investment and research and development than low-skilled immigrants, and productivity effects would be expected to be highest for immigrants in scientific and engineering fields. By raising the demand for housing, immigration also spurs residential investment. However, residential investment is unlikely to expand enough to prevent housing costs from rising, which has implications for income distribution in society.
Keywords: F20; F22; J61; O30; 330; immigration; innovation; foreign direct investment; residential investment; productivity